Implications of Change/Stability Patterns in Children’s Non-symbolic and Symbolic Magnitude Judgment Abilities Over One Year: A Latent Transition Analysis - Chew, Cindy S.; Forte, Jason D.; Reeve, Robert A. (Frontiers in Psychology, 2019)
Nonsymbolic magnitude abilities are often claimed to support the acquisition of symbolic magnitude abilities, which, in turn, are claimed to support emerging math abilities. However, not all studies find links between nonsymbolic and symbolic magnitude abilities, or between them and math ability. To investigate possible reasons for these different findings, recent research has analysed differences in nonsymbolic/symbolic magnitude abilities using latent class modelling and has identified four different magnitude ability profiles residing within the general magnitude ability distribution that were differentially related to cognitive and math abilities. These findings may help explain the different patterns of findings observed in previous research. To further investigate this possibility, we (1) attempted to replicate earlier findings, (2) determine whether magnitude ability profiles remained stable or changed over one year; and (3) assessed the degree to which stability/change in profiles were related to cognitive and math abilities. We used latent transition analysis to investigate stability/changes in nonsymbolic and symbolic magnitude abilities of 109 5- to 6- year olds twice in one year. At time 1 and 2, nonsymbolic and symbolic magnitude abilities, number transcoding and single-digit addition abilities were assessed. Visuospatial working memory (VSWM), naming numbers, non-verbal IQ, basic RT was also assessed at time 1. Analysis showed stability in one profile and changes in the three others over one year. VSWM and naming numbers predicted profile membership at time 1 and 2, and profile membership predicted math abilities at both time points. The findings confirm the existence of four different nonsymbolic–symbolic magnitude ability profiles; we suggest the changes over time in them potentially reflect deficit, delay, and normal math developmental pathways.